Challenges Facing English Language Education in Myanmar: A Narrative Inquiry - Oo, Nang Sandi; Fernandez Deocampo, Marilyn (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
The civil disobedience movement (CDM) has reshaped Myanmar's future and profoundly altered its educational landscape. Amidst this upheaval, critical stakeholders, including administrators, the government, and teachers, struggled to maintain the essential foundation of the nation: education. Like people in other countries, the people of Myanmar aspire to improve their quality of life and education, particularly in learning English. This study employed a narrative approach, using narrative writing texts to explore the lived experiences of English teachers working in international and private schools during this period of instability. Through qualitative methodology, the study collected and analyzed personal stories, revealing the multifaceted challenges faced by these educators. Thematic analysis of the narratives uncovered a range of professional, personal, social, emotional, and legal challenges that deeply impacted their lives. Key themes identified include financial hardships, social isolation, emotional stress, legal threats, and the loss of qualified teachers, leading to a decline in teaching standards and student learning outcomes. By capturing the voices of these teachers through their narratives, the study highlights the complex and far-reaching effects of the CDM on Myanmar's education system.